Neuroinvasion and Neurotropism by SARS-CoV-2 Variants in the K18-hACE2 Mouse - Frauke Seehusen; Jordan J. Clark; Parul Sharma; Eleanor G. Bentley; Adam Kirby; Krishanthi Subramaniam; Sabina Wunderlin-Giuliani; Grant L. Hughes; Edward I. Patterson; Benedict D. Michael; Andrew Owen; Julian A. Hiscox; et al. (Viruses, 2022)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) not only affects the respiratory tract but also causes neurological symptoms such as loss of smell and taste, headache, fatigue or severe cerebrovascular complications. Using transgenic mice expressing human angiotensin-converting enzyme 2 (hACE2), we investigated the spatiotemporal distribution and pathomorphological features in the CNS following intranasal infection with SARS-CoV-2 variants, as well as after prior influenza A virus infection. Apart from Omicron, we found all variants to frequently spread to and within the CNS. Infection was restricted to neurons and appeared to spread from the olfactory bulb mainly in basally oriented regions in the brain and into the spinal cord, independent of ACE2 expression and without evidence of neuronal cell death, axonal damage or demyelination. However, microglial activation, microgliosis and a mild macrophage and T cell dominated inflammatory response was consistently observed, accompanied by apoptotic death of endothelial, microglial and immune cells, without their apparent infection. Microgliosis and immune cell apoptosis indicate a potential role of microglia for pathogenesis and viral effect in COVID-19 and the possible impairment of neurological functions, especially in long COVID. These data may also be informative for the selection of therapeutic candidates and broadly support the investigation of agents with adequate penetration into relevant regions of the CNS.